Competing C‐4 and C‐5‐Acyl Stabilization of Uronic Acid Glycosyl Cations. Issue 63 (12th September 2022) - Elferink, Hidde; Remmerswaal, Wouter A.; Houthuijs, Kas J.; Jansen, Oscar; Hansen, Thomas; Rijs, Anouk M.; Berden, Giel; Martens, Jonathan; Oomens, Jos; Codée, Jeroen D. C.; Boltje, Thomas J.
Abstract: Uronic acids are carbohydrates carrying a terminal carboxylic acid and have a unique reactivity in stereoselective glycosylation reactions. Herein, the competing intramolecular stabilization of uronic acid cations by the C‐5 carboxylic acid or the C‐4 acetyl group was studied with infrared ion spectroscopy (IRIS). IRIS reveals that a mixture of bridged ions is formed, in which the mixture is driven towards the C‐1, C‐5 dioxolanium ion when the C‐5, C‐2‐relationship is cis, and towards the formation of the C‐1, C‐4 dioxepanium ion when this relation is trans . Isomer‐population analysis and interconversion barrier computations show that the two bridged structures are not in dynamic equilibrium and that their ratio parallels the density functional theory computed stability of the structures. These studies reveal how the intrinsic interplay of the different functional groups influences the formation of the different regioisomeric products. Abstract : Uronic acids have a unique reactivity in stereoselective glycosylation reactions. The competing intramolecular stabilization in uronic acid cations by the C‐5 carboxylic acid or the C‐4 acetyl group was studied using infrared ion spectroscopy and computational energy landscape maps. This reveals how the intrinsic interplay of the different functional groups influences the formation of the different regioisomeric products.